Over-aging: Are present human populations too old? - Robert Stelter (Universität Rostock, Institut für Volkswirtschaftslehre, 2014)
This paper investigates the problem of an population" concerning age structures in a 3-period OLG-model with endogenous fertility and longevity. The first-best solution for a number-dampened total social welfare function, including Millian and Benthamite utilitarianism as two extreme cases, identifies the optimal age structure, generally failed in the laissez-faire economy. Individuals over-invest in health expenditures and choose a non-optimal number of offspring. A calibration exercise for 80 countries emphasizes that mean ages in the optimal solution with the highest feasible individual utility exceed the observed in all countries, especially due to a very low first-best number of children. Introducing a preference for the population stock in the social welfare function increases fertility, but reduces individual utility, in the first-best solution. Optimal mean age shrinks and an over-aging of the laissez-faire economy becomes more likely. To decentralize first-best solutions health expenditures are taxed, whereas children are either taxed or subsided.
Keywords: H20; I10; J18; 330; endogenous fertility; adult mortality; optimal age structure; over-aging; optimal taxation